Trends in base hydrolysis rates of Chlorocobalt(III) complexes of a series of related Pentaamine ligands - Baran, Yakup; Comba, Peter; Lawrance, Geoffrey A. (Inorganic reaction mechanisms, 2002)
Base hydrolysis kinetics of chloropentaaminecobalt(III) complexes of a range of acyclic and cyclic pentaamine ligands, incorporating the rigid -NH-CH 2 -C(CH 3 )(NH 2 )-CH 2 -NH- motif, which must coordinate facially in octahedral complexes, are analysed in terms of ground state structural influences on hydrolysis rates. For complexes without experimental structural data, molecular mechanics was used to predict Co-Cl and Co-N bond distances. The computed strain energies and structural parameters both isomers ( trans and cis ) of all compounds are analysed. Although sterically crowded ligands, which should favour a five-coordinate intermediate, exhibit larger k OH values, only a modest correlation between ground state Co-L distances and hydrolysis rates is found. This suggests that the structures of the transition state and/or of the five-coordinate intermediate is important.